Applicability evaluation of smart readiness indicator for buildings - Eloranta, Vilppu (2020)
Buildings are a major energy consumer in the European Union, and only few existing buildings are classified as energy efficient. The EU has established energy directives to enhance energy performance and sustainability of the built environment, including through smart technologies. Therefore, the Smart Readiness Indicator (SRI) for Buildings method is being developed and expected to become a standard procedure to assess buildings based on their readiness to increase performance using smart technologies. This master's thesis considers usage of SRI especially in the Nordic environment. The aims were to recognize benefits of the method and assess its applicability. The objectives were to classify and compare SRI with other building rating systems and analyse real SRI assessment results. Material was acquired in a case study, in which ten public buildings in South Karelia, Finland were SRI assessed. SRI was found to support digitalization of buildings and to identify especially the flexibility required by future energy systems. Transparency and assessment simplicity were also considered advantages. However, the current version did not fully recognize all energy demand flexibility and storage methods, such as virtual power plant system controlling ventilation or heat storage capacity integrated in district heating networks. Additionally, some assessment domains were not considered relevant in the Nordic environment. SRI was recognized as a potentially useful tool in building development activities, provided that the results are interpreted correctly and other assessments performed properly. To facilitate this, a tool was drafted, which would identify essential smartness deficiencies in the building and provide automatic suggestions for improvement. Rakennukset kuluttavat merkittävän osan energiasta Euroopan unionissa, ja vain pieni osa nykyisistä rakennuksista luokitellaan energiatehokkaiksi. EU:n energiadirektiiveillä pyritään parantamaan rakennetun ympäristön energiatehokkuutta ja kestävyyttä mm. älykkäiden ...